New Central American and Mexican Enoclerus Gahan (Coleoptera: Cleridae: Clerinae): Part II - Rifkind, Jacques (Zootaxa, 2012)
The following nineteen new species are described: Enoclerus anctus, E. hespenheidei and E. citricornis from Costa Rica;E. boquete and E. opitzi from Panamá; E. skillmani, E. melissae and E. urbanus from Costa Rica and Panamá; E. mcnallyi,E. fibrillatus, E. toledoi, E. boblloydi, E. chamelae, E. mocho, E. albidulus and E. crinitus from México; E. gilli and E.regnadkcin from Guatemala; E. cavei from El Salvador. In addition, E. silbermannii aeternitatis n. subsp. is describedfrom El Salvador and Costa Rica. The biogeography of the genus in México and Costa Rica is discussed, based on life zone and habitat records for 95 species.